HUBUNGAN MENGKONSUMSI TABLET FE DENGAN KEJADIAN KONSTIPASI PADA IBU HAMIL DI DESA BANDAR KECAMATAN BANDAR KABUPATEN PACITAN - Catur Wulan; Wulan Ayu Fitria (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
Consumption of iron tablet 1 tablet per day during pregnancy can cause constipation. Based on the results of preliminary study in the Bandar Village, Pacitan through interviews with 14 pregnant women there were 12 pregnant women who consumed iron tablet regularly and 8 pregnant women complain of difficulty to defecate while not experiencing constipation 4 pregnant women. From two pregnant women who did not consume fe tablets they didn’t get constipation. The purpose of this study was to determine the relationship consuming Fe tablet with constipation in pregnant women. This type of research is quantitative with cross sectional design conducted in March 2016. The population of all pregnant women in Bandar Village Bandar Subdistrict District of Pacitan as many as 33 pregnant women. The respondents ware all pregnant women in the Bandar Village Bandar district Pacitan. Using total sampling technique, the research was conducted on March 1 until March 30, 2016. The variable in this study is the fe tablet intake and incidence of constipation. The research instrument used was observation about fe tablet consumption and interviewing about incidence of constipation. The data were tabulated and analyzed using a statistical test Chi Square test determined significant with p> 0.05. From the results showed that majority of 19 pregnant women (57.5%) consume iron tablet regularly, and majority of 18 pregnant women (54.5%) got constipation. There was a relationship consuming Fe tablet constipation with in pregnant women in the Bandar Village district ofPacitan. Evidenced by the significant level of 0.000> 0.05 so that Ho refused. Based on the results of the study, the researcher suggested to health workers to provide counseling to pregnant women about how to consume tablets fe correetly and balanced with foods contaiming high in fiber.